Polymorphism of MTHFR C677T Gene and the Associations with the Severity of Essential Hypertension in Northern Chinese Population - Junli Song; Jie Hou; Qiang Zhao; Xuezhi Liu; Qian Guo; Donghong Yin; Yan Song; Xiaoxia Li; Shuyun Wang; Xinchun Wang; Jinju Duan (International Journal of Hypertension)
Objective. Methylenetetrahydrofolate reductase (MTHFR) is a key enzyme of homocysteine metabolism and is closely related to the occurrence of hypertension. The aim of this study was to investigate the polymorphism of the (MTHFR) C677T and the factors influencing the severity of hypertension. Material and Methods. A total of 985 subjects were enrolled to analyze the polymorphisms of the MTHFR C677T gene by polymerase chain reaction (PCR). 306 people with essential hypertension were selected from 985 subjects to estimate the severity of hypertension by the ordinal multivariate logistical regression model. Results. The frequencies of CC, CT, and TT genotypes were 19.5%, 49.95%, and 30.46%, respectively. The allelic frequency of mutant T was 55.43%. The plasma homocysteine level of the homozygous TT in individuals was significantly higher than in those with CC or CT P<0.01. MTHFR677CT genotype, MTHFR677TT genotype, smoking, family history of hypertension, Hcy, and triglycerides (TG) were independent risk factors for the severity of hypertension (OR = 2.29, 2.24, 2.04, 1.81, 1.04, 1.26). Conclusion. MTHFR gene, smoking, family history of hypertension, Hcy, and triglycerides could be important genetic and high-risk factors of the development of severe hypertension in northern Chinese. These factors will contribute to the identification of high-risk populations of hypertension and facilitate the development of hypertension control strategies.